Design, Synthesis, and Biological Evaluation of Pyrazole Derivatives. (11th January 2016) - Hu, Chunqi; Gao, Yali; Du, Wenting
Abstract : In this in vitro study, a series of novel pyrazole derivatives were designed, synthesized, and evaluated against five human cancer cell lines (PC3, A549, HL60, HCT116, and SW620) for their antiproliferative and p53‐MDM2 binding inhibitory activities. Although biological evaluations showed that this series of compounds possessed weak p53‐MDM2 inhibitory activities, most of them displayed moderate to potent antiproliferative activities against the tested cells lines. Compound11c exhibited the best potency for MDM2 (FP‐IC50 = 29.22 μ m ) and demonstrated antiproliferative activities in response to the five tested cell lines (IC50 = 4.09–16.82 μ m ). Compared with the positive control Nutlin‐1, there was enhanced antiproliferative activity to p53‐mutated or p53‐deficient cell lines (SW620, HL60, and PC3). Abstract : A series of novel pyrazole derivatives were designed, synthesized, and evaluated for their p53‐MDM2 binding inhibitory activities and antiproliferation activities in vitro against five humor cancer cell lines (PC3, A549, HL60, HCT116, and SW620). Although these compounds exhibited weak p53‐MDM2 inhibitory activities (29.22 NA μ m ), most of them displayed a moderate to potent anti‐proliferative activities against the tested cells lines. One of them even showed an enhanced antiproliferative activity than Nutlin‐1 to p53 mutated or p53 deficient cell lines (SW620, HL60, and PC3).